Relationship of Sleep Quality with Short-Term Memory and Reaction Time in First Year Medical Students of Diponegoro University - Rizki Gatot Febrian; Santoso Jaeri; Muflihatul Muniroh; Darmawati Ayu Indraswari (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Abstract Background: Sleep disturbance is a disorder that includes a lack of quantity and quality of sleep. Students, especially medical students, have a high risk of getting sleep disorders of poor sleep quality and quantity. Poor sleep quality can interfere with memory. Besides, poor sleep quality also results in fatigue, which can lead to increased reaction time.Aim: To determine the relationship between sleep quality and short-term memory and reaction time in first-year medical students of Diponegoro University.Methods: This Observational study used a cross-sectional design with first-year medical students of Diponegoro University as the subjects. Kolmogorov-Smirnov was applied as the normality test, then the hypothesis test between sleep quality and short-term memory used the Pearson Chi-Square test, while sleep quality and reaction time used the Mann-Whitney U test. Results: Two hundred students participated in the study. Eighty two people (41%) had good sleep quality, 118 people (59%) had poor sleep quality. The p value of the relationship between sleep quality and short-term memory showed insignificant result (p=0.791). Meanwhile, the Mann-Whitney test to measure the relationship between sleep quality and reaction time was also insignificant (p=0.270).Conclusion: There is no significant relationship between sleep quality with reaction time and short-term memory in first-year medical students of Diponegoro University.